2021
DOI: 10.1093/ehjci/jeab227
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial efficiency in patients with different aetiologies and stages of heart failure

Abstract: Aims Myocardial external efficiency (MEE) is the ratio of cardiac work in relation with energy expenditure. We studied MEE in patients with different aetiologies and stages of heart failure (HF) to discover the role and causes of deranged MEE. In addition, we explored the impact of patient characteristics such as sex, body mass index (BMI), and age on myocardial energetics. Methods and results Cardiac energetic profiles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…On the other hand, the presence of LV concentric/eccentric remodeling implicated a myocardial energy metabolism imbalance. A meta-analysis explored myocardial efficiency in patients with different etiologies and stages of HF and demonstrated that myocardial contractility progressively decreased with the reduction of myocardial efficiency in AS patients symptomatic HFrEF (38). The reduction of energy utilization efficiency was caused by decreased creatine kinase activity and phosphocreatine/adenosine triphosphate ratio in AS patients (38,39).…”
Section: Aortic Valve Damages and Hfrefmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the presence of LV concentric/eccentric remodeling implicated a myocardial energy metabolism imbalance. A meta-analysis explored myocardial efficiency in patients with different etiologies and stages of HF and demonstrated that myocardial contractility progressively decreased with the reduction of myocardial efficiency in AS patients symptomatic HFrEF (38). The reduction of energy utilization efficiency was caused by decreased creatine kinase activity and phosphocreatine/adenosine triphosphate ratio in AS patients (38,39).…”
Section: Aortic Valve Damages and Hfrefmentioning
confidence: 99%
“…A meta-analysis explored myocardial efficiency in patients with different etiologies and stages of HF and demonstrated that myocardial contractility progressively decreased with the reduction of myocardial efficiency in AS patients symptomatic HFrEF (38). The reduction of energy utilization efficiency was caused by decreased creatine kinase activity and phosphocreatine/adenosine triphosphate ratio in AS patients (38,39). These findings indicated that AS patients had not only hemodynamic abnormalities resulting from mechanical damage to the valves but also had damage of myocardial function.…”
Section: Aortic Valve Damages and Hfrefmentioning
confidence: 99%
“…Other domains of cardiac phenotyping are continuously evolving [ 57 ]. A number of omics technologies are available that can contribute to the biological characterization of these patients and various computational methods are being investigated for the utilization of large amounts of data to identify pathways of disease [ 58 60 ]. Techniques such as MR spectroscopy may further contribute to our understanding of ongoing energy deficits in these patients [ 61 ].…”
Section: How Can Disease Etiology and Underlying Disease Activity Inf...mentioning
confidence: 99%
“… 93–95 Furthermore, it may be reduced in the presence of relatively preserved ejection fraction as shown in patients with hypertrophic cardiomyopathy, 96 cardiac amyloidosis, 97 and severe valvular heart disease. 91 , 95 Myocardial efficiency is directly associated with systolic dysfunction and inversely related to afterload, activation of the sympathetic nervous system, increased wall stress and left ventricular hypertrophy, 93 , 94 , 98 the contributions of each varying depending on aetiology, and stage of the underlying cardiac disease. Although myocardial oxygen consumption may be similar or even reduced in heart failure when compared with healthy controls, it is increased in relation to mechanical work.…”
Section: Introductionmentioning
confidence: 99%